2020
DOI: 10.1029/2020pa003958
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Western Boundary Current Stability in the North Atlantic Ocean for the Past 700 Kyr From Globorotalia truncatulinoides Coiling Ratios

Abstract: Down-core changes in the coiling direction of Globorotalia truncatulinoides in the northwestern subtropical Atlantic (KNR140-37PC and Ocean Drilling Program Sites 1063, 1059, 1056, 1058) provide a tracer for the hydrographic conditions in the western boundary current over the past 700 kyr (Marine Isotope Stage, MIS, 1-17). A consistent association between percent G. truncatulinoides (sinistral) abundances, total test counts, and bulk sediment CaCO 3 content is established by MIS 11 suggesting a response to oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The near absence of G. inflata, a temperate water mass indicator (~8-18 • C) associated with the NAC in the NE Atlantic [64,65], at sites U1304 [25] and U1314 and core M23414, further corroborates the dominance by the polar and subpolar water masses at these sites during MIS 6. Billups et al [66] suggested compression of the subtropical gyre due to the southward advancement of the Polar and Arctic fronts during glacial times; however, the extent to which such a physical mechanism operated at Site U1313 cannot be assessed due simply to the lack of Globorotalia truncatulinoides (sinistral) data for MIS 6 period.…”
Section: Subpolar To Subtropical Water Mass Movement During Mismentioning
confidence: 99%
“…The near absence of G. inflata, a temperate water mass indicator (~8-18 • C) associated with the NAC in the NE Atlantic [64,65], at sites U1304 [25] and U1314 and core M23414, further corroborates the dominance by the polar and subpolar water masses at these sites during MIS 6. Billups et al [66] suggested compression of the subtropical gyre due to the southward advancement of the Polar and Arctic fronts during glacial times; however, the extent to which such a physical mechanism operated at Site U1313 cannot be assessed due simply to the lack of Globorotalia truncatulinoides (sinistral) data for MIS 6 period.…”
Section: Subpolar To Subtropical Water Mass Movement During Mismentioning
confidence: 99%